Corporate Governance of Banks in Poland and Slovenia - Polona Pašić; Borut Bratina; Mejra Festić (Naše gospodarstvo/Our economy, 2016)
This paper focuses on the analysis of the characteristics of corporate governance in banks in Poland and Slovenia between 2005 and 2013. It studies the impact of corporate governance in these banks on their performance. The results of our research show that Slovenia achieved lower average scores for the variables and indicators related to the transparency of corporate governance than Poland. The density of banks with the highest corporate governance index scores was higher in Poland than in Slovenia. When examining the impact of corporate governance on bank performance as measured with net interest income, the regression analysis showed that its impact is positive in both countries and that it is statistically significant in Slovenia.